The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1186/s13075-019-1870-6
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol levels are elevated in older men with diffuse cutaneous SSc and are associated with decreased survival

Abstract: Background Systemic sclerosis (SSc) is a female-predominant disease, characterized by excessive extracellular matrix deposition (ECM) with dermal and internal organ fibrosis. Considering the sex-based disparity in disease incidence, estradiol (E2), an estrogen form with pro-fibrotic effects, may play a role in SSc. We reported that post-menopausal women with diffuse cutaneous (dc)SSc have higher serum E2 levels compared to similar aged, healthy controls. Since males with SSc tend to have more seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…We extend those findings in this report to suggest that ERα signaling blockade can also prevent E2-induced Col22A1 transcription ex vivo . These results, in conjunction with our previous findings showing that circulating E2 levels are elevated in patients with SSc [ 20 ] suggest that fulvestrant is a promising therapeutic option in patients with SSc.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We extend those findings in this report to suggest that ERα signaling blockade can also prevent E2-induced Col22A1 transcription ex vivo . These results, in conjunction with our previous findings showing that circulating E2 levels are elevated in patients with SSc [ 20 ] suggest that fulvestrant is a promising therapeutic option in patients with SSc.…”
Section: Discussionsupporting
confidence: 86%
“…Our group has shown that E2 levels are increased in post-menopausal women with SSc, and E2 induced dermal thickening and increased fibronectin (FN) in an ex vivo human skin organ culture model and in primary human dermal fibroblasts [ 19 ]. Elevated E2 levels in patients with SSc are associated with reduced survival [ 20 ], suggesting a role for E2 in SSc-fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a large-scale longitudinal study demonstrated that untreated hypogonadism in men increases the risk of both lupus and rheumatoid arthritis (104). Moreover, men with autoimmune thyroid disease and diffuse cutaneous systemic sclerosis have been shown to have higher levels of circulating estradiol compared to unaffected males (105)(106)(107). Together, these studies indicate a protective role of testosterone in autoimmunity.…”
Section: The Role Of Sex Hormones In Autoimmunitymentioning
confidence: 99%
“…However, conversion of testosterone to E2 by aromatase results in healthy older males having higher levels of circulating E2 than postmenopausal women. This is also associated with older males having increased adipose tissue, in which aromatase is expressed [ 3 ]. We have previously shown a significant reduction (43%) in serum 17β-estradiol (E2) [ 25 ] with no significant difference in the level of circulating testosterone after treatment of adult male rats with letrozole.…”
Section: Discussionmentioning
confidence: 99%